THE USE OF GAME TECHNOLOGY IN INTENSIFYING THE PROCESS OF TEACHING ENGLISH LANGUAGE - Akhmedova, Mashkhura (Журнал иностранных языков и лингвистики, 2021)
Abstract Under the game-based training of any subject, including the future profession, we developed the technology of teaching, in which it is given preference to play as the most effective form of reading. As a result of such an experimental study, in addition to the above-mentioned characteristics, the following characteristics have been identified that allow us to examine language and speech games as one of the most effective factors. Due to the fact that the game is superior to the study, the clarification of the educational process is the most effective and economical, since in this case, as a rule, it does not require large expenses for the purchase of tools for its support, and the form of the game itself is the closest to the real professional conditions of future. Key words: game technology, research games, imitation games, nonimitation games, collective activity, language games, active mastering exercises, educational opportunities.